KEMANDIRIAN PEREMPUAN JAWA DALAM CERITA TRADISIONAL - Harjito Harjito (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2014)
This study aims to investigate Javanese women’s autonomy in traditional stories.The data sources were four traditional story texts. The data were collected throughdocumentation. They were analyzed by means of the text analysis technique. The findingsare as follows. First, the unavoidable life passage for adult Javanese women is marriage.In a marriage between a man and a woman, their statuses are unequal. The latter dependson the former. Second, a woman’s autonomy is apparent when she is left behind by herhusband, because of either his death or his offended feeling. There are three types ofJavanese women’s autonomy in traditional stories, namely protecting and taking care ofchildren, becoming leaders, and being loyal to authorities.